Perubahan Kebiasaan Pesta Pernikahan Pada Masyarakat Bolaang Mongondow - Nasruddin Yusuf; Rizal Lahati; Vindri M. Adampe; Faradila Hasan (Al-Mizan (e-Journal), 2022)
This article aims to describe the pattern of changes in the habits of wedding parties carried out by the Bolaang Mongondow community. The method used in this study is a qualitative method using an empirical sociological approach. The celebration of the wedding party as a tradition that grows and develops in the community must be in line with Islamic law and the norms in the community. Although currently, its implementation is experiencing obstacles due to cultural acculturation, so it will be difficult to distinguish between right and wrong. From the observations, it is known that the implementation of the wedding party in Bolaang Mongondow is indicated to be forced (lavishly) even though the cost of the wedding party is beyond the ability of the person who carries it out.